2012
DOI: 10.1073/pnas.1120764109
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with plant transcription factors can mediate nuclear import of phytochrome B

Abstract: Phytochromes (phy) are red/far-red-absorbing photoreceptors that regulate the adaption of plant growth and development to changes in ambient light conditions. The nuclear transport of the phytochromes upon light activation is regarded as a key step in phytochrome signaling. Although nuclear import of phyA is regulated by the transport facilitators far red elongated hypocotyl 1 (FHY1) and fhy1-like, an intrinsic nuclear localization signal was proposed to be involved in the nuclear accumulation of phyB. We rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 47 publications
(82 reference statements)
3
74
0
1
Order By: Relevance
“…Interestingly, PIF-induced phyB degradation does not operate under prolonged shade environments (Leivar et al, 2012a), consistent with the absence of interaction between PIFs and the Pr-inactive form of phy or under SD photoperiods (Soy et al, 2012), where the short light period is insufficient to promote significant slow PIF3-induced phyB degradation. Adding another layer of complexity, it has been reported that the interaction with PIFs mediates the nuclear import of phyB into isolated nuclei of the algae Acetabularia acetabulum (Pfeiffer et al, 2012). Consistent with this observation, the authors showed that phyB is not translocated into the nucleus of Arabidopsis pifq mutants during early irradiation of dark-grown seedlings.…”
Section: Pif Function In Phy-mediated Growth Responses To Light Phy Rsupporting
confidence: 75%
“…Interestingly, PIF-induced phyB degradation does not operate under prolonged shade environments (Leivar et al, 2012a), consistent with the absence of interaction between PIFs and the Pr-inactive form of phy or under SD photoperiods (Soy et al, 2012), where the short light period is insufficient to promote significant slow PIF3-induced phyB degradation. Adding another layer of complexity, it has been reported that the interaction with PIFs mediates the nuclear import of phyB into isolated nuclei of the algae Acetabularia acetabulum (Pfeiffer et al, 2012). Consistent with this observation, the authors showed that phyB is not translocated into the nucleus of Arabidopsis pifq mutants during early irradiation of dark-grown seedlings.…”
Section: Pif Function In Phy-mediated Growth Responses To Light Phy Rsupporting
confidence: 75%
“…Phys containing the G767R mutation are retained in the cytoplasm (Wagner and Quail, 1995;Ni et al, 1999;Matsushita et al, 2003). This has been attributed to the inability of the G767R mutant to interact with PIF3 and then be imported into the nucleus (Pfeiffer et al, 2012). Surprisingly, the double phy mutant partially complemented the phyABCDE null mutant: light-grown YHB-G767R(phyABCDE) lines exhibited expanded cotyledons and shorter hypocotyls compared with the parental phyABCDE seedlings (Fig.…”
Section: Cytosolic Yhb Has Little Effect On Clock Gene Expression or mentioning
confidence: 98%
“…Recently, the pif4 pif5 double loss-of-function mutant has been shown to be hypersensitive to low FR fluence rates, without altering phyA concentration (Lorrain et al, 2009). PIF3 facilitates the nuclear import of phyB under R and FR light irradiation (Pfeiffer et al, 2012). Thus, PIFs may be involved in phyB-mediated repression of seedling deetiolation under FR light (Figure 10).…”
Section: Phyb Enhances Spa1 Accumulation To Repress Fr Light Signalinmentioning
confidence: 99%